Brewing Arizona : A Century of Beer in the Grand Canyon State - Sipos, Ed (Book collections on Project MUSE., 2013)
"Sergeant there is a brewery here!" shouted Private Lutje into the tent of his commanding officer. His regiment had just set up camp outside of Tucson. It was spring. The year was 1866. And the good private had reason to be shocked. How could anyone brew beer in the desert? The water was alkaline (when it was fit to drink at all), grains were scarce, bottles were in short supply, and refrigeration was nearly non-existent. But human ingenuity cannot be overestimated, especially when it comes to creating alcoholic beverages. Since 1864, the state's breweries have had a history as colorful as the state. With an eye like a historian, the good taste of a connoisseur, and the tenacity of a dedicated collector, author Ed Sipos serves up beer history with gusto. Brewing Arizona is the first book of Arizona beer. It includes every brewery known to have operated in the state, from the first to the latest, from crude brews to craft brews, from mass beer to microbrews. This eye-opening chronicle is encyclopedic in scope but smooth in its delivery. Like a fine beer, the contents are deep and rich, with a little froth on top. With more than 250 photographs200 in full color Brewing Arizona is as beautiful as it is tasty. So put up your feet, grab a cold one, and sip to your heart's delight.